Low-carbon renewable fabric based on modified soybean protein fibers as well as preparation method and application of low-carbon renewable fabric
By combining modified soy protein fiber and nanotechnology, low-carbon renewable fabrics are prepared, solving the problem of poor degradability of traditional fabrics and achieving improved environmental protection performance and durability of the fabrics.
Patent Information
- Application Number
- CN202510300324.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-14
AI Technical Summary
Traditional textile fabrics have poor degradability and are difficult to decompose naturally after being discarded, resulting in environmental pollution and waste of resources.
The preparation method of low-carbon renewable fabrics based on modified soy protein fiber is adopted, and the nanofiber membrane is formed through processes such as soaking, low-temperature freezing and crushing, ultrasonic treatment, spray drying and hot pressing composite, and the surface performance of the fabric is improved through plasma treatment.
The fabric is achieved with low carbon and environmentally friendly performance, improves its degradability and durability, ensures that it can be naturally decomposed after being discarded, and reduces environmental pollution and resource waste.
Smart Images

Figure CN119820930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fabric preparation, and in particular to a low-carbon renewable fabric based on modified soybean protein fiber and a preparation method and application thereof. Background Art
[0002] With the rapid advancement of industrialization, the massive consumption of energy has led to a continuous increase in greenhouse gas emissions, and the trend of global warming has continued to intensify. Environmental problems such as air pollution, water pollution, and soil pollution have emerged in an endless stream, seriously threatening human survival and development. At the same time, the over-exploitation and use of non-renewable resources have led to a decrease in resource reserves, and a resource crisis is imminent. Against this backdrop, all fields are actively exploring the path of sustainable development, and the textile industry is no exception.
[0003] The production of traditional textile fabrics is often accompanied by high energy consumption, the use of a large number of chemicals, and dependence on non-renewable resources. During the production process, a large amount of electricity, coal and other energy sources are consumed, which not only increases production costs, but also leads to a large amount of greenhouse gas emissions. At the same time, in order to achieve various properties of fabrics, such as dyeing and wrinkle resistance, a large amount of chemicals are used. These chemicals will release harmful substances during production and use, causing serious harm to the environment and human health.
[0004] In addition, traditional fabrics have poor biodegradability and are difficult to decompose naturally after being discarded. A large amount of textile waste accumulates in the environment, placing a heavy burden on the ecosystem. These wastes not only occupy land resources, but also pollute soil and water sources. Summary of the invention
[0005] The technical problem to be solved by the present invention is that traditional fabrics have poor biodegradability and are difficult to decompose naturally after being discarded.
[0006] To this end, the first aspect of the present invention mentions a method for preparing a low-carbon renewable fabric based on modified soybean protein fiber, comprising: Step S110: soaking the soybean protein fiber in a solution containing a natural antioxidant, taking out the soybean protein fiber, and then freezing and crushing the soybean protein fiber to a nanometer particle size to obtain nanometer soybean protein fiber particles; Step S210: mixing the nano-scale soybean protein fiber particles, the green modifier and the nano-magnetic particles in a mass ratio of 1: (0.1-0.3): (0.05-0.15) to form a mixed system, and subjecting the mixed system to ultrasonic treatment. During the ultrasonic treatment, carbon dioxide gas is introduced at a preset temperature and a preset pressure; Step S310: the modified soybean protein fiber particles are mixed with natural cellulose fibers and biodegradable polymer nanofibers to obtain a composite system, the composite system is spread on a flat plate with micropores at the bottom, and a mixed solution of aerogel powder and polyvinyl alcohol with a mass concentration of 5%-10% is evenly sprayed on the composite system by a spray device. After the spraying is completed, the composite system is dried at a temperature of 40-60° C. for 3-5 hours to obtain a nanofiber membrane; Step S410: Plasma treatment is performed on the nanofiber membrane, and multiple layers of the plasma-treated nanofiber membrane are composited by hot pressing to obtain a low-carbon renewable fabric.
[0007] Furthermore, step S310 includes: grinding the silica aerogel powder to control the particle size to be 1-5 microns.
[0008] Furthermore, the green modifier is one or more of chitosan, sodium alginate, protease and lipase.
[0009] Furthermore, during the ultrasonic treatment of the mixed system, the ultrasonic frequency and power are intermittently changed; the initial ultrasonic frequency and the initial ultrasonic power are determined, and the mixed system is ultrasonically treated; after a first preset time, the ultrasonic frequency is adjusted to a secondary ultrasonic frequency and a secondary ultrasonic power, and the ultrasonic treatment is continued; after a second preset time, the ultrasonic frequency is changed back to the initial ultrasonic frequency and the initial ultrasonic power, and the cycle is repeated until the ultrasonic treatment process is completed.
[0010] Furthermore, the modified soybean protein fiber particles, natural cellulose fibers and biodegradable polymer nanofibers are mixed in a mass ratio of 1: (0.2-0.5): (0.1-0.3) to obtain a composite system.
[0011] Furthermore, the natural antioxidant is one of vitamin C, vitamin E, tea polyphenols, anthocyanin, coenzyme Q10, and glutathione; the nanomagnetic particles are one or more of MnZnFe2O4 nanoparticles, NiZnFe2O4 nanoparticles, CoFe nanoparticles, and FeNi nanoparticles; further, the biodegradable polymer nanofibers are one or more of polylactic acid nanofibers, polycaprolactone nanofibers, polyhydroxyalkanoate nanofibers, and chitosan nanofibers; and the natural cellulose fibers are one or more of cotton fibers, hemp fibers, and wood pulp fibers.
[0012] Furthermore, the temperature of low-temperature freezing and crushing is -50°C to -80°C, the nano-scale particle size is 1-100 nanometers; the preset temperature is 30-60°C, and the preset pressure is 5-15MPa.
[0013] The second aspect of the present application mentions a low-carbon renewable fabric based on modified soy protein fiber, which is prepared using the preparation method of a low-carbon renewable fabric based on modified soy protein fiber mentioned in the first aspect above.
[0014] The third aspect of the present application mentions the application of a low-carbon renewable fabric based on modified soybean protein fiber in clothing.
[0015] The beneficial effects of the present application are as follows: the present invention mentions a low-carbon renewable fabric based on modified soybean protein fiber and its preparation method and application, wherein the method comprises: soaking the soybean protein fiber in a solution containing a natural antioxidant, taking out the soybean protein fiber and subjecting the soybean protein fiber to low-temperature freezing and crushing, crushing to nanometer particle size, and obtaining nanometer-scale soybean protein fiber particles; mixing the nanometer-scale soybean protein fiber particles with a green modifier and nanomagnetic particles to form a mixed system, and ultrasonically treating the mixed system, and during the ultrasonic treatment, introducing carbon dioxide gas at a preset temperature and a preset pressure; mixing the modified soybean protein fiber particles with natural cellulose fibers and biodegradable polymer nanofibers to obtain a composite system, spreading the composite system on a flat plate with micropores at the bottom, spraying aerogel powder and polyvinyl alcohol on the composite system by a spray device, and after the spraying is completed, drying the composite system to obtain a nanofiber membrane; plasma-treating the nanofiber membrane, and hot-pressing and compounding the multi-layer plasma-treated nanofiber membrane to obtain a low-carbon renewable fabric.
[0016] The low-carbon renewable fabric mentioned in this application adopts a new modified soybean protein fiber. By modifying it, the molecular structure of the fiber is protected, oxidative damage is reduced, and the stability and subsequent reaction activity of the fiber particles are improved, laying the foundation for multiple recycling and degradability. Secondly, advanced materials such as green modifiers and nanomagnetic particles are introduced to combine with soybean protein fibers under specific conditions to form more stable chemical bonds. While enhancing the performance of the fabric, these components can be degraded or reused in the natural environment or under specific treatment conditions. Furthermore, the modified soybean protein fiber particles are mixed with natural cellulose fibers and biodegradable polymer nanofibers, and the introduction of aerogel powder and other fiber composites further improves the overall thermal insulation capacity of the fabric. The fabric structure formed by the hot-pressing composite of multi-layer nanofiber membranes is tight, which reduces the conduction and loss of heat and jointly ensures good thermal insulation performance. Finally, through processes such as plasma treatment and hot-pressing composite, the surface properties of the fiber membrane are further improved, its surface activity and adhesion are increased, and the bonding between the multi-layer fiber membranes is made more firm, while improving the durability of the fabric, it does not affect its degradable performance, ensuring that the fabric can be naturally decomposed after being discarded and return to the natural cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below based on the specifics of the present invention and in conjunction with the accompanying drawings.
[0018] Figure 1 The present invention is a flowchart of a method for preparing a low-carbon renewable fabric based on modified soybean protein fiber. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with the accompanying drawings and details so that those skilled in the art can better understand the present invention and implement it, but the examples are not intended to limit the present invention.
[0020] refer to Figure 1 The first aspect of the present invention mentions a method for preparing a low-carbon renewable fabric based on modified soybean protein fiber, comprising: step S110: soaking the soybean protein fiber in a solution containing a natural antioxidant, taking out the soybean protein fiber and subjecting it to low-temperature freezing and crushing, crushing it to a nanometer particle size, and obtaining nanometer-scale soybean protein fiber particles.
[0021] It should be noted that the temperature of low-temperature freezing and crushing is -50℃ to -80℃, and the size of nano-scale particles is 1-100 nanometers. If the size of the nano-scale particles is too large, it will affect the subsequent mixing uniformity with other substances. When mixed with green modifiers, larger particles are difficult to fully contact and react, resulting in poor modification effects. If the size of the nano-scale particles is too small, the surface energy of the particles will increase, making them more likely to agglomerate. This will in turn affect subsequent processing, requiring more energy and special dispersion methods to prevent agglomeration. At the same time, it will also affect the mechanical properties of the fiber, resulting in reduced fiber strength and affecting the durability of the final fabric.
[0022] For example, a small planetary ball mill can be used, the speed of the ball mill is set at 300-500 rpm, and the grinding time is controlled at 10-15 hours. After the initial crushing in the ball mill, the crushed particles are classified using a screen. The larger particles that have not reached the nanometer size are returned to the ball mill for secondary crushing, and through multiple classification and crushing cycles, more particles are gradually made to reach the target nanometer size.
[0023] Specifically, the soy protein fiber can be cryogenically frozen and crushed to nanometer particle size to obtain nanometer soy protein fiber particles. Before freezing and crushing, the soy protein fiber is first soaked in a natural antioxidant for a period of time. The use of natural antioxidants can protect the molecular structure of the soy protein fiber during the crushing process, reduce the oxidative damage caused by mechanical crushing, and improve the stability of the fiber particles and the subsequent reaction activity.
[0024] In the technical scheme, the natural antioxidant is one of vitamin C, vitamin E, tea polyphenols, anthocyanidins, coenzyme Q10, and glutathione.
[0025] Step S210: Mix the nano-scale soybean protein fiber particles with the green modifier and the nano-magnetic particles to form a mixed system, and perform ultrasonic treatment on the mixed system. During the ultrasonic treatment, introduce carbon dioxide gas at a preset temperature and a preset pressure.
[0026] Specifically, nano-scale soybean protein fiber particles are mixed with green modifiers and nano-magnetic particles in a mass ratio of 1: (0.1-0.3): (0.05-0.15), and nano-magnetic particles are added to the mixed system. The nano-magnetic particles can generate a local micromagnetic field during the ultrasonic treatment process, promote the combination of green modifiers and soybean protein fiber particles, and improve the modification efficiency. At the same time, in the subsequent processing process, the external magnetic field can be used to align the fibers and enhance the mechanical properties of the fabric. After the introduction of carbon dioxide gas, the catalytic effect of the nano-magnetic particles is used to promote the reaction of carbon dioxide with the fibers and modifiers to form a more stable chemical bond.
[0027] In the technical solution, the green modifier is one or more of chitosan, sodium alginate, protease and lipase.
[0028] In the technical solution, the nanomagnetic particles are one or more of MnZnFe2O4 nanoparticles, NiZnFe2O4 nanoparticles, CoFe nanoparticles, and FeNi nanoparticles.
[0029] In this technical solution, the preset temperature is 30-60°C, and the preset pressure is 5-15MPa.
[0030] It should be noted that if the temperature is lower than 30°C, it is difficult for carbon dioxide to reach a supercritical state. At the same time, its solubility in the system is low, which affects the effect on the mixed system. If the temperature is higher than 60°C, it will have an adverse effect on the performance of soybean protein fiber, green modifier and nano-magnetic particles, leading to protein denaturation and modifier decomposition.
[0031] It should be noted that if the pressure is lower than 5 MPa, it is also difficult for carbon dioxide to reach a good supercritical state, and the penetration and effect on the mixed system are weakened. In addition, a pressure lower than 5 MPa will result in insufficient modification of the fiber.
[0032] In this technical solution, the ultrasonic frequency and power can be changed intermittently during the ultrasonic treatment process. Different ultrasonic frequencies and powers can produce different cavitation effects and mechanical effects, which help to break the local balance of the reaction system, make the reaction more complete, and improve the uniformity of the modification effect.
[0033] Specifically, the initial ultrasonic frequency and the initial ultrasonic power are first determined, and the mixed system is ultrasonically treated; after the first preset time, the ultrasonic frequency is adjusted to the secondary ultrasonic frequency, the power is the secondary ultrasonic power, and the ultrasonic treatment is continued; after the second preset time again, the ultrasonic frequency is changed back to the initial ultrasonic frequency and the initial ultrasonic power, and the cycle is carried out until the ultrasonic treatment process ends. The present application can improve the uniformity of the mixed system through intermittent ultrasonic treatment, because different ultrasonic frequencies and powers can produce different cavitation effects and mechanical vibration effects in the mixed system. Intermittently changing the frequency and power can make the various components in the mixed system move and mix under different forces, avoiding the local uneven treatment phenomenon under a single frequency and power, thereby improving the treatment uniformity of the entire system. In addition, by changing the frequency and power, the nanomagnetic particles, soy protein fiber particles and green modifiers can interact at different energy levels to promote their better dispersion and mixing. This helps to improve the performance stability and consistency of the final product.
[0034] Step S310: The modified soybean protein fiber particles are mixed with natural cellulose fibers and biodegradable polymer nanofibers to obtain a composite system, the composite system is spread on a flat plate with micropores at the bottom, and a mixed solution of aerogel powder and polyvinyl alcohol with a mass concentration of 5%-10% is evenly sprayed on the composite system using a spray device. After the spraying is completed, the composite system is dried at a temperature of 40-60°C for 3-5 hours to obtain a nanofiber membrane.
[0035] In this technical solution, the mass of aerogel powder is controlled to be 5%-20% of the total mass of the fiber mixing system. Within this range, aerogel can better fill the internal pores of the fiber and adhere to the fiber surface, effectively improving the thermal insulation performance of the fabric without significantly increasing the weight and cost of the fabric. When the amount of aerogel powder is too little, it cannot fully fill the fiber pores and it is difficult to form an effective thermal insulation barrier; when the amount is too much, the fabric will be too thick, affecting its comfort and processing performance.
[0036] Specifically, silica aerogel is prepared. The aerogel is ground to refine its particle size to 1-5 microns. The modified soybean protein fiber particles, natural cellulose fibers and biodegradable polymer nanocomposite system are spread flat in a special container, and a microporous plate is set at the bottom of the container. The aerogel powder and the mixed liquid of polyvinyl alcohol with a mass concentration of 5%-10% are evenly sprayed on the composite system using a spray device. During the spraying process, the exhaust device of the microporous plate at the bottom of the container is started to form a stable airflow, so that the aerogel powder can be better filled into the internal pore structure of the fiber and attached to the fiber surface under the action of the airflow. After the spraying is completed, the composite system is dried at a temperature of 40-60°C for 3-5 hours to solidify the polyvinyl alcohol and fix the bonding state of the aerogel and the fiber.
[0037] In a feasible implementation, a sand mill is used for wet grinding. The sand mill drives the grinding medium to rotate at high speed through an agitator to grind and disperse the material. The grinding medium can be glass beads or ceramic beads.
[0038] It should be noted that adding a small amount of biodegradable polymer nanofibers can increase the strength and toughness of the fiber membrane, while improving the degradability of the fabric, meeting the requirements of low-carbon and environmental protection.
[0039] It should be noted that the mass ratio of the modified soybean protein fiber particles to natural cellulose fibers and biodegradable polymer nanofibers is controlled to be 1: (0.2-0.5): (0.1-0.3). If the proportion of natural cellulose fibers is too high, the fabric will be too rough and lose the softness of the soybean protein fibers.
[0040] In the technical solution, the natural cellulose fiber is one or more of cotton fiber, hemp fiber and wood pulp fiber.
[0041] In the technical solution, the biodegradable polymer nanofiber is one or more of polylactic acid nanofiber, polycaprolactone nanofiber, polyhydroxyalkanoate nanofiber, and chitosan nanofiber.
[0042] Step S410: Plasma treatment is performed on the nanofiber membrane, and multiple layers of the plasma-treated nanofiber membrane are composited by hot pressing to obtain a low-carbon renewable fabric.
[0043] Before hot pressing and laminating, the nanofiber membrane is subjected to plasma treatment. Specifically, the nanofiber membrane is subjected to plasma treatment using a radio frequency plasma generating device with a treatment power of 50-100W and a treatment time of 10-20 minutes. Plasma treatment can improve the surface properties of the fiber membrane, increase its surface activity and adhesion, improve the effect of hot pressing and laminating, and make the bonding between the multi-layer fiber membranes more solid.
[0044] The low-carbon renewable fabric of modified soybean protein fiber mentioned in this application, first of all, soybean protein fiber itself has natural renewability, wide sources and environmental protection. By modifying it, its performance can be further improved to make it more suitable for recycling. In the modification process, the soybean protein fiber is treated with natural antioxidants, which can not only protect the molecular structure of the fiber, reduce oxidative damage, improve the stability and subsequent reaction activity of the fiber particles, but also provide guarantee for multiple recycling. Secondly, green modifiers and nano-magnetic particles and other materials are introduced, and under specific temperature, pressure and ultrasonic treatment conditions, they are combined with soybean protein fibers to form more stable chemical bonds and enhance the performance of the fabric. These ingredients can be degraded or reused in the natural environment or under specific treatment conditions, laying the foundation for the recycling of fabrics. Furthermore, the modified soybean protein fiber particles are mixed with natural cellulose fibers and biodegradable polymer nanofibers, and the introduction of aerogel powder and other fiber composites further improves the overall thermal insulation capacity of the fabric; the fabric structure formed by the hot pressing composite of multi-layer nanofiber membranes is tight, which reduces the conduction and loss of heat and jointly ensures good thermal insulation performance. Finally, through plasma treatment and hot pressing composite process, the surface properties of the fiber membrane are further improved, its surface activity and adhesion are increased, the bonding between the multi-layer fiber membranes is made stronger, the durability of the fabric is improved, and strong support is provided for recycling.
[0045] The second aspect of the present application mentions a low-carbon renewable fabric based on modified soybean protein fiber, which is prepared by a preparation method of a low-carbon renewable fabric based on modified soybean protein fiber as mentioned in the first aspect above. In terms of environmental protection, soybean protein fiber is treated with natural antioxidants, combined with green modifiers and nanomagnetic particles, carbon dioxide gas is introduced at environmentally friendly preset temperature and pressure, natural cellulose fibers and biodegradable polymer nanofibers are added, the use of chemical substances is reduced, the adverse effects on the environment are reduced, degradability is enhanced and excessive pollution is not generated. In addition, it has good economic performance, low raw material cost, low production energy consumption, and renewable and degradable characteristics make it recyclable after the product life cycle ends, reducing resource waste. At the same time, the fabric is comfortable, soybean protein fiber and natural cellulose fiber are combined with skin-friendly and comfortable, suitable for close-fitting wear, and has good air permeability and hygroscopicity. In addition, it also has certain antibacterial properties, natural antioxidants and green modifiers can inhibit bacterial growth, reduce odor generation, and provide users with a healthy wearing experience.
[0046] In order to better understand the technical solution, the technical solution of the present invention is described in detail below by way of embodiments.
[0047] Example 1 BASF's vitamin C products were selected as natural antioxidants, the green modifier was chitosan produced by Qingdao Mingyue Blue Ocean Biotechnology Co., Ltd., the nanomagnetic particles were MnZnFe2O4 nanoparticles produced by Nanjing Xianfeng Nanomaterials Technology Co., Ltd., the natural cellulose fiber was cotton fiber produced in Xinjiang, and the biodegradable polymer nanofiber was polylactic acid nanofiber produced by Zhejiang Hisun Biomaterials Co., Ltd.
[0048] The soy protein fiber is soaked in a 1g / L vitamin C solution, taken out and rinsed, and the fiber is centrifugally dehydrated to a water content of 10%-20%, and then cryogenically frozen and crushed at -50°C to a nano-scale particle size of 50 nanometers.
[0049] Nano-scale soybean protein fiber particles are mixed with chitosan and MnZnFe2O4 nanoparticles in a mass ratio of 1:0.1:0.15. The mixed system is subjected to ultrasonic treatment, with an initial ultrasonic frequency of 40kHz and an initial ultrasonic power of 800W. After the first preset time of 15 minutes, the ultrasonic frequency is adjusted to 35kHz and the power is adjusted to 700W. After 15 minutes, the ultrasonic frequency and power are adjusted back to the initial ultrasonic frequency and power, and the cycle is repeated. The ultrasonic treatment is carried out at a preset temperature of 45°C and a preset pressure of 10MPa. Carbon dioxide gas is introduced according to a mass ratio of soybean protein fiber to carbon dioxide of 1:0.1.
[0050] Disperse silica aerogel in water to form a slurry with a concentration of 10%-20%. Add the slurry to a sand mill and add grinding media in a volume ratio of 1:2-1:3 between the slurry and the grinding media. Set the stirring speed of the sand mill to 1500-3000 rpm and the grinding time to 5-10 hours. During the grinding process, the slurry is repeatedly ground through the sand mill through a circulation system. After the grinding is completed, the grinding media is separated from the aerogel slurry by centrifugal separation, and then the slurry is dried to obtain an aerogel powder with a particle size of 1-5 microns.
[0051] The modified soybean protein fiber particles, cotton fibers and polylactic acid nanofibers in a mass ratio of 1:0.2:0.3 are mixed to obtain a composite system, and the composite system is spread on a flat plate with micropores at the bottom. A mixed solution of aerogel powder with a mass of 1 / 20 of the composite system and polyvinyl alcohol with a mass concentration of 5% is evenly sprayed on the composite system using a spray device. After spraying, the composite system is dried at a temperature of 40-60°C for 3-5 hours to obtain a nanofiber membrane.
[0052] The nanofiber membrane is treated with a radio frequency plasma generating device with a processing power of 50W and a processing time of 20 minutes, and then hot-pressed and composited to form the fabric.
[0053] The antioxidant effect of vitamin C protects the molecular structure of soy protein fiber. Chitosan and polylactic acid nanofibers themselves are highly biodegradable. The nanoscale fiber particle structure increases the contact area with microorganisms, allowing the fabric to be decomposed by microorganisms more quickly.
[0054] Example 2 The natural antioxidants selected were tea polyphenols produced by Zhejiang New Silver Elephant Bioengineering Co., Ltd., the green modifier was a mixture of sodium alginate produced by Qingdao Mingyue Seaweed Group Co., Ltd. and protease produced by Zhejiang New Silver Elephant Bioengineering Co., Ltd., and the nanomagnetic particles were NiZnFe2O4 nanoparticles produced by Nanjing Xianfeng Nanomaterials Technology Co., Ltd. The natural cellulose fibers were hemp fibers produced by Jiangsu Zijinghua Textile Technology Co., Ltd., and the biodegradable polymer nanofibers were polycaprolactone nanofibers produced by Zhuhai Maidefa Biomaterials Co., Ltd.
[0055] The soy protein fiber is soaked in a solution containing tea polyphenols, taken out and rinsed, and the fiber is centrifugally dehydrated to a water content of 10%-20%, and then cryogenically frozen at -65°C and crushed to a nano-scale particle size of 80 nanometers.
[0056] Nano-scale soybean protein fiber particles, a mixture of sodium alginate and protease, and NiZnFe2O4 nanoparticles are mixed in a mass ratio of 1:0.2:0.10. The mixed system is subjected to ultrasonic treatment, with an initial ultrasonic frequency of 45kHz and an initial ultrasonic power of 900W. After the first preset time of 20 minutes, the ultrasonic frequency is adjusted to a secondary ultrasonic frequency of 40kHz and the power is adjusted to a secondary ultrasonic power of 800W. After 20 minutes, the ultrasonic frequency and power are adjusted back to the initial ultrasonic frequency and power, and the cycle is repeated. The ultrasonic treatment is carried out at a preset temperature of 50°C and a preset pressure of 12MPa, and carbon dioxide gas is introduced at a mass ratio of soybean protein fiber to carbon dioxide of 1:0.1.
[0057] Disperse silica aerogel in water to form a slurry with a concentration of 10%-20%. Add the slurry to a sand mill and add grinding media in a volume ratio of 1:2-1:3 between the slurry and the grinding media. Set the stirring speed of the sand mill to 1500-3000 rpm and the grinding time to 5-10 hours. During the grinding process, the slurry is repeatedly ground through the sand mill through a circulation system. After the grinding is completed, the grinding media is separated from the aerogel slurry by centrifugal separation, and then the slurry is dried to obtain an aerogel powder with a particle size of 1-5 microns.
[0058] The modified soybean protein fiber particles, hemp fiber and polycaprolactone nanofibers in a mass ratio of 1:0.4:0.2 are mixed to obtain a composite system, and the composite system is spread on a flat plate with micropores at the bottom. A mixed solution of aerogel powder with a mass of 1 / 10 of the composite system and polyvinyl alcohol with a mass concentration of 10% is evenly sprayed on the composite system using a spray device. After spraying, the composite system is dried at a temperature of 40-60°C for 3-5 hours to obtain a nanofiber membrane.
[0059] The nanofiber membrane is treated with a radio frequency plasma generating device with a processing power of 75W and a processing time of 15 minutes, and then hot-pressed to form a fabric.
[0060] The antioxidant properties of tea polyphenols protect the molecular structure of soybean protein fiber. The modification of sodium alginate and protease combined with the good degradability of hemp fiber and polycaprolactone nanofibers, coupled with the nano-scale fiber particle structure, increases the contact area with microorganisms, making the fabric faster to be decomposed by microorganisms in the natural environment. At the same time, nano-magnetic particles can promote the decomposition of microorganisms to a certain extent.
[0061] Example 3 The natural antioxidant selected is anthocyanin produced by Zhejiang Xinyinxiang Bioengineering Co., Ltd., the green modifier is lipase produced by Qingdao Mingyue Seaweed Group Co., Ltd., the nanomagnetic particles are CoFe nanoparticles produced by Nanjing Xianfeng Nanomaterial Technology Co., Ltd., the natural cellulose fiber is wood pulp fiber produced by Jiangsu Bauhinia Textile Technology Co., Ltd., and the biodegradable polymer nanofiber is chitosan nanofiber produced by Qingdao Mingyue Seaweed Group Co., Ltd.
[0062] The soy protein fiber is soaked in a solution containing anthocyanins, taken out and rinsed, and the fiber is centrifugally dehydrated to a water content of 10%-20%, and then cryogenically frozen at -80°C and crushed to a nano-scale particle size of 30 nanometers.
[0063] Nano-scale soybean protein fiber particles were mixed with lipase and CoFe nanoparticles in a mass ratio of 1:0.3:0.05. The mixed system was subjected to ultrasonic treatment, with an initial ultrasonic frequency of 38kHz and an initial ultrasonic power of 750W. After the first preset time of 12 minutes, the ultrasonic frequency was adjusted to a secondary ultrasonic frequency of 35kHz and the power was adjusted to a secondary ultrasonic power of 700W. After 12 minutes, the ultrasonic frequency and power were adjusted back to the initial ultrasonic frequency and power, and the cycle was repeated. The ultrasonic treatment was carried out at a preset temperature of 40°C and a preset pressure of 8MPa. Carbon dioxide gas was introduced according to a mass ratio of soybean protein fiber to carbon dioxide of 1:0.1.
[0064] Disperse silica aerogel in water to form a slurry with a concentration of 10%-20%. Add the slurry to a sand mill and add grinding media in a volume ratio of 1:2-1:3 between the slurry and the grinding media. Set the stirring speed of the sand mill to 1500-3000 rpm and the grinding time to 5-10 hours. During the grinding process, the slurry is repeatedly ground through the sand mill through a circulation system. After the grinding is completed, the grinding media is separated from the aerogel slurry by centrifugal separation, and then the slurry is dried to obtain an aerogel powder with a particle size of 1-5 microns.
[0065] The modified soybean protein fiber particles, wood pulp fibers and chitosan nanofibers in a mass ratio of 1:0.5:0.1 are mixed to obtain a composite system, and the composite system is spread on a flat plate with micropores at the bottom. A mixed solution of aerogel powder with a mass of 1 / 5 of the composite system and polyvinyl alcohol with a mass concentration of 15% is evenly sprayed on the composite system using a spray device. After the spraying is completed, the composite system is dried at a temperature of 40-60°C for 3-5 hours to obtain a nanofiber membrane.
[0066] The nanofiber membrane is treated with a radio frequency plasma generating device with a processing power of 100W and a processing time of 10 minutes, and then hot-pressed to form a composite fabric.
[0067] Thermal insulation performance test experiment: 1. Experimental equipment: Flat plate heat flow meter: used to measure heat flow. Environmental test chamber: can accurately control environmental conditions such as temperature and humidity, with a temperature control accuracy of ±0.5°C and a relative humidity control accuracy of ±3%. Sample frame: used to fix the sample to ensure that the sample is flat during the test. Data acquisition system: connected to the flat plate heat flow meter to record heat flow data; 2. Sample preparation: Cut the fabrics prepared in Example 1, Example 2, and Example 3 into a circular shape with a diameter of 300 mm, and ensure that the sample has no defects such as damage and wrinkles. Prepare 3 samples for each example; 3. Experimental steps Environmental condition setting: Set the temperature of the environmental test box to 20°C and the relative humidity to 65%, and start the test after the environment stabilizes. Install the sample flatly on the sample frame, and then place it in the measurement area of the flat-plate heat flow meter to ensure that the sample is in good contact with the heat flow meter. Measure heat flow: Turn on the data acquisition system and record the heat flow changes of the sample within a certain period of time. The measurement time should be no less than 30 minutes until the heat flow data is stable. Calculate the thermal insulation performance index: Calculate the thermal insulation rate based on the heat flow data; 4. Result determination: The average value and standard deviation of the test results of the three samples of the fabrics prepared in Example 1, Example 2, and Example 3 are calculated, as shown in Table 1 below.
[0068]
[0069] According to Table 1, the fabrics prepared in Example 1, Example 2, and Example 3 are all greater than 30% of the national standard, and the standard deviation is within a reasonable range of no more than 3%.
[0070] Degradability test experiment using soil burial method: 1. Experimental materials and equipment Experimental soil: Select fertile, unpolluted garden soil or farmland soil, sieve to remove impurities and larger particles, and adjust the soil moisture to 60%-70% of the field water holding capacity. Culture container: such as plastic flower pots or glass culture dishes, with a diameter of about 150-200mm and air holes. Balance: with an accuracy of 0.01g, used to weigh the sample mass. Constant temperature incubator: The temperature is controlled at 25℃±2℃; 2. Sample preparation: The fabrics prepared in Example 1, Example 2, and Example 3 were cut into small pieces of about 20 mm × 20 mm in size, and the initial mass of each small piece was accurately weighed. At least 5 samples were prepared for each example; 3. Experimental steps Soil burial: Spread a layer of experimental soil about 50mm thick on the bottom of the culture container, bury the sample evenly in the soil, and then cover it with a layer of soil about 20mm thick. Culture observation: Place the culture container in a constant temperature incubator, regularly observe the soil moisture, replenish water in time, and keep the soil moisture stable. Quality determination: Take out the samples at the 7th, 14th, 21st, and 28th days, gently rinse off the surface soil with clean water, and after naturally air-drying in a cool place, weigh the sample mass with a balance and calculate the degradation rate; 4. Result determination: The average value and standard deviation of the test results of the three samples of the fabrics prepared in Example 1, Example 2, and Example 3 are calculated, as shown in Table 2 below.
[0071]
[0072] According to Table 2, the degradation rates of the fabrics prepared in Example 1, Example 2, and Example 3 reached 11%-18%.
[0073] Obviously, the above is only an example for clear explanation and is not a limitation of the implementation method. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
[0074] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0075] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0076] In the present invention, unless otherwise clearly specified and limited, when a first feature is “on” or “below” a second feature, it may be that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, when a first feature is “above”, “above” or “above” a second feature, it may be that the first feature is directly above or obliquely above the second feature, or it may simply mean that the first feature is higher in level than the second feature. When a first feature is “below”, “below” or “below” a second feature, it may be that the first feature is directly below or obliquely below the second feature, or it may simply mean that the first feature is lower in level than the second feature.
[0077] In the description of this specification, the description of the terms "one", "some", "examples", "specific examples" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the or examples are included in at least one or examples of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different or examples and the features of the different or examples described in this specification without contradiction.
[0078] Although the present invention has been shown and described above, it is to be understood that the above is exemplary and is not to be construed as limiting the present invention. A person skilled in the art may make changes, modifications, substitutions and variations to the above within the scope of the present invention.
Claims
1. A method for preparing a low-carbon renewable fabric based on modified soybean protein fiber, characterized in that: include: Step S110: soaking the soybean protein fiber in a solution containing a natural antioxidant, taking out the soybean protein fiber, and then freezing and crushing the soybean protein fiber to a nanometer particle size to obtain nanometer soybean protein fiber particles; Step S210: mixing the nano-scale soybean protein fiber particles, the green modifier and the nano-magnetic particles in a mass ratio of 1: (0.1-0.3): (0.05-0.15) to form a mixed system, and subjecting the mixed system to ultrasonic treatment. During the ultrasonic treatment, carbon dioxide gas is introduced at a preset temperature and a preset pressure; Step S310: the modified soybean protein fiber particles are mixed with natural cellulose fibers and biodegradable polymer nanofibers to obtain a composite system, the composite system is spread on a flat plate with micropores at the bottom, and a mixed solution of aerogel powder and polyvinyl alcohol with a mass concentration of 5%-10% is evenly sprayed on the composite system by a spray device. After the spraying is completed, the composite system is dried at a temperature of 40-60° C. for 3-5 hours to obtain a nanofiber membrane; Step S410: performing plasma treatment on the nanofiber membrane, and performing hot pressing on the multi-layer plasma treated nanofiber membrane to obtain a low-carbon renewable fabric.
2. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: Step S310 includes: grinding the silica aerogel powder to control the particle size to be 1-5 microns.
3. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: The green modifier is one or more of chitosan, sodium alginate, protease and lipase.
4. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: During the ultrasonic treatment of the mixed system, the ultrasonic frequency and power are intermittently changed; the initial ultrasonic frequency and the initial ultrasonic power are determined, and the mixed system is ultrasonically treated; after a first preset time, the ultrasonic frequency is adjusted to a secondary ultrasonic frequency and the power is adjusted to a secondary ultrasonic power, and the ultrasonic treatment is continued; after a second preset time, the ultrasonic frequency is changed back to the initial ultrasonic frequency and the initial ultrasonic power, and the cycle is repeated until the ultrasonic treatment process is completed.
5. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: The modified soybean protein fiber particles, natural cellulose fibers and biodegradable polymer nanofibers are mixed in a mass ratio of 1: (0.2-0.5): (0.1-0.3) to obtain a composite system.
6. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: The natural antioxidant is one of vitamin C, vitamin E, tea polyphenols, anthocyanin, coenzyme Q10, and glutathione; the nanomagnetic particles are one or more of MnZnFe2O4 nanoparticles, NiZnFe2O4 nanoparticles, CoFe nanoparticles, and FeNi nanoparticles.
7. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: The biodegradable polymer nanofibers are one or more of polylactic acid nanofibers, polycaprolactone nanofibers, polyhydroxyalkanoate nanofibers, and chitosan nanofibers; the natural cellulose fibers are one or more of cotton fibers, hemp fibers, and wood pulp fibers.
8. The method for preparing a low-carbon renewable fabric based on modified soybean protein fiber according to claim 1, characterized in that: The temperature of low-temperature freezing and crushing is -50°C to -80°C, the size of the nano-scale particles is 1-100 nanometers; the preset temperature is 30-60°C, and the preset pressure is 5-15MPa.
9. A low-carbon renewable fabric based on modified soybean protein fiber, prepared by the preparation method of a low-carbon renewable fabric based on modified soybean protein fiber as described in any one of claims 1 to 8.
10. Use of the low-carbon renewable fabric based on modified soybean protein fiber as claimed in claim 9 in clothing.
Citation Information
Patent Citations
Preparing method of soybean protein film for packaging
CN110204752A
Modified soybean protein fiber, antibacterial composite fabric and preparation and application thereof
CN116065391A
Flame-retardant heat-insulating layer-shaped composite fabric and preparation method thereof
CN119590043A